Metal-Free Synthesis of Pyrrolo[1,2-a]quinoxalines Mediated by TEMPO Oxoammonium Salts - Huo, Heng-rui; Tang, Xiang-Ying; Gong, Yue-fa (Synthesis, 2018)
We herein describe a novel TEMPO oxoammonium salt initiated Pictet–Spengler reaction of imines, generated in situ from carbonyl compounds and pyrrole- or indole-containing substrates, to afford 4,5-dihydropyrrolo[1,2-a]quinoxalines or 5,6-dihydroindolo[1,2-a]quinoxalines in good to excellent yields. Moreover, a one-pot synthesis of a biologically important quinoxaline is achieved via a cyclization–dehydrogenation process using one equivalent of the oxoammonium salt.
Keywords: TEMPO oxoammonium salts; Pictet–Spengler reaction; imines; dihydroquinoxalines; quinoxalines